Pengolahan Sampah Rumah Tangga Dengan Menerapkan Prinsip 3R (Reduce , Reuse, Recycle) Kepada Masyarakat - Maftukhah, Nur Afni; Wulandari, Asputri; Wulandari, Febri; Al Falif, Rifqoh; Dwi Eka Paksi, Kartika; Ananda, Dea; Purnama Putri, Aguilira; S, Herlisa; -, Sendagia; Aprilia Putri, Cindy; Ali, RM Farhan (Universitas Muhammadiyah Palembang, 2025)
Waste processing using the waste burning method can have an impact on air pollution and health, waste processing using 3R (Reduce, Reuse, Recycle) can be an effort to reduce waste by reusing, reducing, recycling waste so that it has added value and also reduces waste in the community. The methods used are questionnaires and counseling. The results obtained were that many people had a poor level of knowledge about burning waste.